A welcoming town near the Thai border - Abu Bakar, Munaarfah (New Straits Times, 2014)
TWO years ago when we decided that enough was enough, and we didn't want to be a weekend husband and wife anymore, we moved from Kuala Lumpur to the tiny, sleepy town of Changlun, Kubang Pasu, Kedah.When I tried to slot in Changlun as the town where we lived, my Facebook account failed to indicate that it was located in Malaysia.